Exploring the state of educational & care giving services for autistic children in Dhaka city: a case study of two schools - Majumdar, Arpita (BRAC University, 2012)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2011.